Carbonized concrete and preparation method thereof
By combining mineral component design and pre-carbonization process for gelling materials, the technical route of "CO2 premixed mineralization hydration-carbonization-hydration" is adopted, and the problems of insufficient carbon sequestration capacity, difficult molding, unstable strength and difficult alkalinity in the existing carbonization technology are solved, achieving efficient carbon sequestration and mechanical properties improvement.
Patent Information
- Application Number
- CN202310336592.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-03-31
AI Technical Summary
There are many problems with existing carbonization technology, including the failure to fully utilize the carbon sequestration capacity of new low-calcium cement, the materials are difficult to cast and mold after pre-carbonization, the depth of the carbonization reaction is limited, the product strength is unstable, and the system alkalinity is difficult to control.
By designing mineral components of gelled materials and combining with partial pre-carbonization processes, the "CO2 premixed mineralization hydration-carbonization-hydration" technical route is adopted to achieve early mold release strength and subsequent strength growth of the product, while regulating the alkalinity of the concrete system.
It improves the carbon sequestration ability and mechanical properties of concrete, achieves long-term stable strength growth of products, maintains the alkalinity controllability of the concrete system, and meets the durability requirements of reinforced concrete.
Smart Images

Figure CN116477881B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ecological building materials, and particularly relates to carbonized concrete and a preparation method thereof. Background Art
[0002] As a major material for engineering construction, concrete has made great contributions to infrastructure construction and the absorption of solid waste. However, cement, the main cementitious material of concrete, has the defects of high energy consumption and high greenhouse gas (CO2) emissions. Many researchers at home and abroad have focused on the carbon reduction of traditional concrete in the early stage. However, the carbonization reaction degree of ordinary concrete itself is low, and concrete products are relatively dense, with limited carbon fixation capacity and still high carbon footprint. New low-carbon cement with carbonated silicate minerals such as C3S2, γ-C2S, and CS as the main components has become a development hotspot and trend due to its advantages of low carbon emissions and carbon fixation.
[0003] Conventional concrete carbonization processes usually place prepared concrete products in a carbonization reaction chamber under certain conditions, and use the carbonated calcium silicate minerals in the concrete to react with carbon dioxide under wet conditions to form calcium carbonate and silica gel, thereby achieving the effects of carbon fixation and reinforcement. The carbonation reaction includes the diffusion of carbon dioxide into the concrete matrix and the mineralization reaction of carbon dioxide with the calcium silicate minerals in the concrete matrix. The diffusion process determines the depth and degree of carbonization and the uniformity of carbonization inside and outside the matrix, and is also an important factor restricting the development of large-scale concrete carbonization products. Relevant scholars have studied the carbonation degree improvement technology and deep carbonization technology. One of the technical ideas is to take pre-carbonization measures, such as: Patent CN105801069A discloses a method for preparing high-carbon-fixing building materials products, which uses a carbonization curing method of stirring (carbonization stirring) combined with curing in a CO2 atmosphere to improve the carbon fixation and strength of traditional cement prefabricated building materials; Patent CN109485354A discloses a method for preparing carbon-fixing concrete prefabricated parts, in the process of ordinary concrete mixing and molding, industrial waste gas containing carbon dioxide is continuously injected for preliminary carbonization, and then the mixture is loaded into the prefabricated part mold and placed in the concrete carbon fixation chamber, and the carbonization curing with mold is obtained to obtain the carbon-fixing concrete prefabricated part. Patent CN114873979A discloses a low-carbon cement concrete and its preparation method, which mainly utilizes the high carbonization activity of low-calcium cement and the catalytic effect of carbon dioxide absorbent to achieve deep carbonization enhancement. However. The existing carbonization technology still has the following problems: ① It only involves the traditional cement concrete pre-carbonization treatment technology, and fails to fully explore the role of the new low-carbon cement concrete pre-carbonization technology in carbon fixation and enhancement; ② The cement and concrete mixture is pre-carbonized as a whole. After pre-carbonization, the mixture is usually dry and loose, difficult to cast and compact, and the structure of the carbonization product is destroyed as a whole; ③ The pursuit of complete carbonization does not consider the later strength growth of the product after carbonization curing and the control of the matrix alkalinity, and is not suitable for reinforced concrete products. ④ Concrete products are usually thin plates, thin walls or porous structures.
[0004] Therefore, how to make full use of the carbonation and carbon fixation capacity of the new low-calcium cement and the pre-carbonization technology to prepare castable low-calcium concrete products, break through the depth limitation of the carbonation reaction, and ensure long-term stability of the product strength and controllable system alkalinity is an urgent problem to be solved. Summary of the invention
[0005] The main purpose of the present invention is to provide a carbonized concrete and a preparation method thereof in view of the problems and shortcomings of the prior art. By designing the mineral components of the cementitious material and combining it with a partial pre-carbonization process, the depth limitation of the carbonization reaction is broken through on the basis of meeting the requirements of the casting and molding process of low-calcium cement concrete, and the long-term stable development of the product strength is achieved. The alkalinity inside the hardened concrete system is controllable, and the carbon fixation capacity and mechanical properties of the concrete can be effectively improved.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A carbonized concrete, wherein the components and their weight proportions include: 280-600 parts of cementitious materials, 700-950 parts of fine aggregate, 800-1200 parts of coarse aggregate, 130-200 parts of water, and 2-12 parts of admixture; wherein the cementitious materials include a hydration active component A, a high carbonization active component B, and a long-acting hydration component C; the hydration active component A is C3S, C3A, The high carbonization active component B is one or more of C3S2, CS, and γ-C2S, and the long-acting hydration component C is β-C2S.
[0008] In the above scheme, the components in the gelling material and their mass percentages include: fast hydration active component A 10-20%, high carbonization active component B 50-80%, and long-term hydration component C 10-30%.
[0009] Preferably, the content of the long-acting hydration component C is 10-25%.
[0010] In the above scheme, in the carbonized concrete, firstly, a part of the cementitious material and all the fine aggregate are added to part of the water, and CO2 gas is introduced for stirring to obtain pre-carbonized cement mortar; then, the pre-carbonized cement mortar is mixed with the remaining cementitious material, coarse aggregate, admixture and remaining water to prepare a concrete mixture; finally, the concrete mixture is formed and carbonized and cured to obtain a carbonized concrete product.
[0011] In the above scheme, the partial amount of cementitious material accounts for 1 / 5 to 1 / 2 of the total amount of cementitious material; the partial amount of water accounts for 1 / 5 to 1 / 2 of the total amount of water.
[0012] In the above scheme, the mass of the CO2 gas is 1-5% of the amount of the gelling material (total gel material).
[0013] The present invention designs the mineral components of the cementitious material, utilizes the hydration reaction of the fast hydration active component A and the CO2 premixed mineralization reaction of the carbonization active component B to provide the early strength of the test piece product, realizes early demoulding, can effectively shorten the mold turnover cycle, improve production efficiency, and save costs; the carbonization active component B provides the main strength and functional requirements of the product in the subsequent carbonization maintenance and enhancement process; the long-term hydration component C is hydrated for a long time during the use of the product to adjust the alkalinity of the concrete system, so that the steel bars in the concrete are in a passivated stable state, and the durability requirements of reinforced concrete are met.
[0014] In the above scheme, the fine aggregate can be selected from at least one of river sand, machine-made sand, river sand and undersize material, with a fineness modulus of 2.0 to 3.2 and a powder content of more than 5wt%.
[0015] In the above scheme, the coarse aggregate can be selected from at least one of pebbles, crushed stones, and recycled aggregates; and a continuous gradation of 5 to 31.5 mm or a continuous gradation of 5 to 20 mm is adopted.
[0016] In the above scheme, the admixture is one or more of naphthalene-based water-reducing agent or melamine water-reducing agent; and the water reduction rate thereof is 15-30%.
[0017] The above-mentioned method for preparing carbonized concrete comprises the following steps:
[0018] 1) Weigh the raw materials according to the proportion, and the components and their weight proportions include: 280-600 parts of cementitious materials, 700-950 parts of fine aggregates, 800-1200 parts of coarse aggregates, 130-200 parts of water, and 2-12 parts of admixtures;
[0019] 2) adding a portion of the cementitious material and all the fine aggregate into a mixer, adding a portion of water, and then introducing CO2 gas into the closed mixer to fully stir the materials in a CO2 atmosphere to obtain pre-carbonized cement mortar;
[0020] 3) adding the remaining amount of cementitious material, coarse aggregate, admixture and remaining water to the obtained pre-carbonated cement mortar, stirring and treating to obtain a pre-carbonated low-carbon cement concrete mixture;
[0021] 4) pouring the mixture into a product mold to form the product, wherein the maximum thickness of the product is not more than 300 mm;
[0022] 5) Place the formed concrete in a dry environment for natural curing and then remove the formwork, and then control the moisture content of the concrete product to 3-7% by drying or humidifying;
[0023] 6) placing the concrete product in a carbonization reactor, and carbonizing and curing for 6 to 24 hours under the conditions of 20 to 100% CO2 gas concentration, 0 to 1.2 MPa pressure, and 30 to 80° C. to obtain a carbonized cement concrete product.
[0024] In the above scheme, the sufficient stirring time in step 2) is 30 to 90 seconds.
[0025] In the above scheme, the stirring treatment time in step 3) is 30 to 160 seconds.
[0026] Furthermore, the obtained carbonized cement concrete product will continue to hydrate during the use or service stage and adjust the alkalinity inside the hardened concrete, so as to put the steel bars in a passivation environment.
[0027] In the preparation process of the present invention, firstly, part of the cementitious material is pre-mixed with CO2 for mineralization. On the one hand, the mineralization reaction between part of the cementitious material and CO2 is promoted to form nano-calcium carbonate and silica gel, which can provide crystal nuclei and ore deposits for subsequent carbonization curing, accelerate the carbonization reaction process, and improve the concrete pore structure by utilizing the filling effect of nano-calcium carbonate. On the other hand, the formed moist and loose mortar-sand mixture can absorb a part of the CO2 that has not undergone the mineralization reaction, and can be used as an internal carbon source for the subsequent carbonization reaction, thereby increasing the carbonization depth of the concrete product and breaking through the limitation of the deep carbonization of large-size component products.
[0028] Conventional low-carbon concrete is mostly devoted to carbonization enhancement during carbonization curing, and pursues complete carbonization, without considering the later strength growth of the product and the control of matrix alkalinity after carbonization curing. Since the carbonization process involves three phases of gas, liquid and solid, it is difficult to achieve a dense degree, and there are still many carbonized channel pores and closed pores in the matrix. The present invention introduces a long-lasting hydration component, which is further hydrated after carbonization enhancement, and uses the hydration product to fill the pores and closed pores of the carbonized channel, compact the concrete pore structure, and improve the mechanical properties and impermeability of the concrete. The low-carbon concrete obtained by the present invention has a significantly reduced matrix alkalinity after carbonization, no color change when spraying a phenolphthalein color developer, and a pH value reduced from about 13.4 before carbonization to about 8.2 after carbonization; when the phenolphthalein color developer is sprayed again after hydration for 7 days or even several months, the matrix appears red, the internal carbonized weak area is particularly obvious, the pH value gradually increases, increases to about 9.6 after hydration for 7 days, and continues to increase to about 13.0 after several months; this indicates that the introduced long-acting hydration component plays a role, continuously releases alkaline substances, improves the matrix alkalinity of the concrete, makes the steel bars in the concrete in a passivated stable state, and meets the long-term durability requirements of the reinforced concrete.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1) The present invention adopts the technical route of "CO2 premixed mineralization hydration-carbonation-hydration". First, CO2 atmosphere premixed mineralization and primary hydration are carried out to provide the early demoulding strength of the test piece product, which is convenient for the process preparation of cast molded products and greatly improves efficiency; the carbonization process provides the main strength and functional requirements of the product; the long-term hydration process makes up for the deficiency of the internal carbonization weak area, fills the pores, and at the same time regulates the alkalinity of the concrete system to maintain the stable state of steel passivation in the concrete, meeting the long-term durability requirements of reinforced concrete;
[0031] 2) Adding coarse aggregate and water to the cement mortar obtained after pre-carbonization, and introducing admixtures to adjust it to a pourable molding state, the molding process involved is simple, the product size and structure are easy to design and control, and the application range is wider;
[0032] 3) The main component of the cementitious material used in the present invention is a low-calcium active component with low carbon emissions and carbon footprint. First, part of the cementitious material is pre-carbonized, and a part of CO2 can be absorbed and consumed during the CO2 atmosphere premixing mineralization process, and then carbon absorption and carbon fixation can continue in the subsequent carbonization curing enhancement process. The synergistic effect of the three can significantly improve the carbon reduction effect of the concrete described in the present invention. DETAILED DESCRIPTION
[0033] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
[0034] In the following examples, the fine aggregate used is the machine-made sand provided by Huaxin Concrete (Wuxue) Co., Ltd., which has a fineness modulus of 3.0 and a powder content of 6.5%; the coarse aggregate is 5-31.5 continuously graded crushed stone provided by Huaxin Concrete (Wuxue) Co., Ltd.; the naphthalene-based water reducer is the FDN-C type powder naphthalene-based water reducer provided by Shandong Wanshan Chemical Co., Ltd., which has a water reduction rate of 25% and a sodium sulfate content of 18%; the melamine water reducer is the melamine-based high-efficiency water reducer provided by Suzhou Xingbang Chemical Building Materials Co., Ltd., which has a water reduction rate of 30%.
[0035] In the following embodiments, the cementitious materials used are obtained by conventional crushing, grinding, batching, homogenization, calcination and grinding, based on the designed mineral composition requirements, using limestone, iron ore and sandstone as raw materials.
[0036] Example 1
[0037] A method for preparing carbonized concrete comprises the following steps:
[0038] 1) Weighing of raw materials, each component and its weight proportion are: 550 weight parts of cementitious material, 752 weight parts of fine aggregate, 948 weight parts of coarse aggregate, 175 weight parts of water, 8.4 weight parts of admixture (naphthalene-based water reducer);
[0039] The components and their mass percentages in the cementitious material used are: fast hydration active component A (C3S) 15%, high carbonization active component B (C3S2) 72%, long-term hydration component C (β-C2S) 10%, and other components are mainly calcium aluminosilicate, iron phase solid solution and inevitable impurities;
[0040] 2) Add 1 / 3 of the cementitious material and all the fine aggregates into a mixer, add 1 / 3 of the water, close the mixer and introduce CO2 gas, stir the materials fully for 60 seconds under the CO2 atmosphere, and obtain pre-carbonized cement mortar; wherein the mass of the introduced CO2 is 3.5% of the amount of cementitious material;
[0041] 3) adding the remaining cementitious material, coarse aggregate, admixture and water to the obtained pre-carbonated cement mortar and stirring for 120 seconds to obtain a pre-carbonated low-carbon cement concrete mixture;
[0042] 4) pouring the obtained mixture into a product mold to form the product, wherein the thickness of the product is 150 mm;
[0043] 5) Place the formed concrete in a dry environment for natural curing for 24 hours before removing the formwork, and then control the moisture content of the concrete product to 5% by drying;
[0044] 6) The obtained concrete product is placed in a carbonization reactor, first evacuated and then introduced with 100% concentration CO2 gas, the pressure in the reactor is controlled at 1.1 MPa and the temperature is 80°C, and carbonization curing is performed for 24 hours to obtain a carbonized cement concrete product.
[0045] After testing, the compressive strength of the concrete product before carbonization (obtained in step 5) obtained in this embodiment is 30.4MPa, the compressive strength of the concrete product after carbonization (obtained in step 6) is 64.8MPa, and the carbon fixation amount is 130kg / m 3 After further standard curing for one month, the compressive strength increased to 67.3 MPa, and the internal pH value was 12.7 when the specimen was split. The obtained carbonized cement concrete product continued to hydrate during the use or service stage.
[0046] Example 2
[0047] A method for preparing carbonized concrete comprises the following steps:
[0048] 1) Weighing of raw materials, each component and its weight proportion are: 450 weight parts of cementitious material, 830 weight parts of fine aggregate, 950 weight parts of coarse aggregate, 160 weight parts of water, 5.8 weight parts of admixture (naphthalene water reducer and melamine water reducer mixed in a mass ratio of 1:1);
[0049] Among them, the components and their mass percentages in the cementitious material used are: fast hydration active component A 15%, high carbonization active component B (CS) 66%, long-term hydration component C (β-C2S) 15%, other components are mainly calcium aluminosilicate, iron phase solid solution and inevitable impurities;
[0050] 2) Add 1 / 2 amount of cementitious material and all fine aggregates into a mixer, add 1 / 2 amount of water, close the mixer and introduce CO2 gas, so that the materials are fully stirred in the CO2 atmosphere for 90 seconds to obtain pre-carbonized cement mortar; wherein the mass of CO2 introduced is 3% of the amount of cementitious material used;
[0051] 3) adding the remaining cementitious material, coarse aggregate, admixture and water to the obtained pre-carbonated cement mortar and stirring for 120 seconds to obtain a pre-carbonated low-carbon cement concrete mixture;
[0052] 4) pouring the obtained mixture into a product mold to form the product, wherein the thickness of the product is 200 mm;
[0053] 5) Place the formed concrete in a dry environment for natural curing for 12 hours before removing the formwork, and then control the moisture content of the concrete product to 3% by drying;
[0054] 6) The obtained concrete product is placed in a carbonization reactor, first evacuated and then introduced with 80% concentration of CO2 gas, the pressure in the reactor is controlled at 0.7 MPa and the temperature is 60°C, and carbonization curing is performed for 20 hours to obtain a carbonized cement concrete product.
[0055] The test showed that the compressive strength of the concrete product before carbonization was 25.6 MPa, the compressive strength of the concrete product after carbonization was 53.9 MPa, and the carbon fixation amount was 115 kg / m 3 After further natural curing for 2 months, the compressive strength increased to 59.4 MPa, and the internal pH value of the split specimen was 13.2; the obtained carbonized cement concrete product continued to hydrate during the use or service stage.
[0056] Example 3
[0057] A method for preparing carbonized concrete comprises the following steps:
[0058] 1) Weighing of raw materials, each component and its weight proportion are: 380 weight parts of cementitious material, 810 weight parts of fine aggregate, 1030 weight parts of coarse aggregate, 155 weight parts of water, 2.7 weight parts of admixture (naphthalene-based water reducer);
[0059] The components and their mass percentages in the cementitious material used are: fast hydration active component A (C3S and C3A mixed in a mass ratio of 1:1) 20%, high carbonization active component B (γ-C2S) 55%, long-term hydration component C (β-C2S) 21%, and other components are mainly calcium aluminosilicate, iron phase solid solution and inevitable impurities;
[0060] 2) Add 1 / 2 amount of cementitious material and all fine aggregates into a mixer, add 1 / 2 amount of water, close the mixer and introduce CO2 gas, stir the materials fully for 60 seconds under CO2 atmosphere, and obtain pre-carbonized cement mortar; wherein the mass of CO2 introduced is 4% of the amount of cementitious material;
[0061] 3) adding the remaining cementitious material, coarse aggregate, admixture and water to the obtained pre-carbonated cement mortar and stirring for 120 seconds to obtain a pre-carbonated low-carbon cement concrete mixture;
[0062] 4) pouring the obtained mixture into a product mold to form the product, wherein the thickness of the product is 200 mm;
[0063] 5) Place the formed concrete in a dry environment for natural curing for 18 hours before removing the formwork, and then control the moisture content of the concrete product to 4% by drying;
[0064] 6) The obtained concrete product is placed in a carbonization reactor, first evacuated and then introduced with 50% concentration CO2 gas, the pressure in the reactor is controlled at 0.6 MPa and the temperature is 50°C, and carbonization curing is performed for 12 hours to obtain a carbonized cement concrete product.
[0065] The test showed that the compressive strength of the concrete product before carbonization was 20.4 MPa, the compressive strength of the concrete product after carbonization was 46.2 MPa, and the carbon fixation amount was 96 kg / m 3 After further curing in water for one month, the compressive strength increased to 49.4 MPa, and the internal pH value was 13.6 when the specimen was split. The obtained carbonized cement concrete product continued to hydrate during the use or service stage.
[0066] Example 4
[0067] A method for preparing carbonized concrete comprises the following steps:
[0068] 1) Weighing of raw materials, each component and its weight proportion are: 380 parts of cementitious material, 910 parts of fine aggregate, 920 parts of coarse aggregate, 165 parts of water, 3.0 parts of admixture (melamine water reducer);
[0069] The components and their mass percentages in the cementitious material used are: fast hydration active component A (C3A) 10%, high carbonization active component B (C3S2 and CS mixed in a mass ratio of 1:1) 71%, long-term hydration component C (β-C2S) 15%, and other components are mainly calcium aluminosilicate, iron phase solid solution and inevitable impurities;
[0070] 2) Add 1 / 5 of the amount of cementitious material and all fine aggregates into a mixer, add half of the amount of water, close the mixer and introduce CO2 gas, so that the materials are fully stirred for 60 seconds in a CO2 atmosphere to obtain pre-carbonized cement mortar; wherein the mass of the introduced CO2 is 2% of the amount of cementitious material used;
[0071] 3) adding the remaining cementitious material, coarse aggregate, admixture and water to the obtained pre-carbonated cement mortar and stirring for 120 seconds to obtain a pre-carbonated low-carbon cement concrete mixture;
[0072] 4) pouring the obtained mixture into a product mold to form the product, wherein the thickness of the product is 300 mm;
[0073] 5) Place the formed concrete in a dry environment for natural curing for 18 hours before removing the formwork, and then control the moisture content of the concrete product to 5% by drying;
[0074] 6) The obtained concrete product is placed in a carbonization reactor, first evacuated and then introduced with 100% concentration CO2 gas, the pressure in the reactor is controlled at 0.5 MPa and the temperature is 70°C, and carbonization curing is performed for 24 hours to obtain a carbonized cement concrete product.
[0075] The test showed that the compressive strength of the concrete product before carbonization was 16.1 MPa, the compressive strength of the concrete product after carbonization was 48.9 MPa, and the carbon fixation amount was 118 kg / m 3 After further natural curing for one month, the compressive strength increased to 53.6 MPa. The internal pH value of the split specimen was 12.2. The obtained carbonized cement concrete product continued to hydrate during the use or service stage.
[0076] Example 5
[0077] A method for preparing carbonized concrete comprises the following steps:
[0078] 1) Weighing of raw materials, each component and its weight proportion are: 380 parts of cementitious material, 910 parts of fine aggregate, 920 parts of coarse aggregate, 165 parts of water, 3.0 parts of admixture (naphthalene-based water reducer);
[0079] The components and their mass percentages in the cementitious material used are: fast hydration active component A (C3A) 10%, high carbonization active component B (C3S2 and CS mixed in a mass ratio of 1:1) 71%, long-term hydration component C (β-C2S) 15%, and other components are mainly calcium aluminosilicate, iron phase solid solution and inevitable impurities;
[0080] 2) Add 1 / 3 of the cementitious material and all the fine aggregates into a mixer, add 1 / 3 of the water, close the mixer and introduce CO2 gas, stir the materials fully for 60 seconds under the CO2 atmosphere, and obtain pre-carbonized cement mortar; wherein the mass of the introduced CO2 is 2% of the amount of cementitious material;
[0081] 3) adding the remaining cementitious material, coarse aggregate, admixture and water to the obtained pre-carbonated cement mortar and stirring for 120 seconds to obtain a pre-carbonated low-carbon cement concrete mixture;
[0082] 4) Embed ribbed steel bars with a diameter of 10 mm in the mold, with the steel bars 50 mm away from the edge of the mold, and both ends of the steel bars extending out of the mold, and then pour the mixture into the product mold to form it, where the thickness of the product is 300 mm;
[0083] 5) Place the formed concrete in a dry environment for natural curing for 24 hours before removing the formwork, and then control the moisture content of the concrete product to 5% by drying;
[0084] 6) The obtained concrete product is placed in a carbonization reactor, first evacuated and then introduced with 100% CO2 gas, the pressure in the reactor is controlled at 0.5 MPa and the temperature is 70°C, and carbonization and curing is performed for 24 hours to obtain a carbonized cement concrete product (reinforced concrete specimen).
[0085] The obtained reinforced concrete specimens were placed in a natural environment for curing, and the changes in the corrosion current density of the steel bars in the concrete products at different ages were tested. The results are shown in Table 1.
[0086] Table 1 Changes in corrosion current density of steel bars in concrete products at different ages
[0087]
[0088] Note: The corrosion current density is less than 0.2μA / cm 2 It indicates that the steel bar is in a passivation state.
[0089] In Table 1, the ordinary concrete used as the control group was made of PO42.5 cement, and the components and their weight proportions were: 360 parts of PO42.5 cement, 920 parts of fine aggregate, 950 parts of coarse aggregate, 175 parts of water, and 4.3 parts of polycarboxylic acid high-efficiency water-reducing agent. It was molded using a conventional preparation process and then placed in a standard curing room for curing for 1 day before demolding.
[0090] It can be seen from Table 1 that the corrosion current density of the steel bars in the concrete products increases to a certain extent in the early stage after carbonization, and then gradually decreases, which is equivalent to that of ordinary concrete, and is always at a low corrosion level. The steel bars are in a passivated state and the corrosion rate is extremely low.
[0091] Comparative Example 1
[0092] A method for preparing carbonized concrete comprises the following steps:
[0093] 1) Weighing of raw materials, each component and its weight proportion are: 380 weight parts of cementitious material, 910 weight parts of fine aggregate, 920 weight parts of coarse aggregate, 165 weight parts of water, 3.0 weight parts of admixture (melamine water reducer);
[0094] The components and their mass percentages in the cementitious material used are: fast hydration active component A (C3A) 10%, high carbonization active component B (C3S2 and CS mixed in a mass ratio of 1:1) 71%, long-term hydration component C (β-C2S) 15%, and other components are mainly calcium aluminosilicate, iron phase solid solution and inevitable impurities;
[0095] 2) adding all the weighed raw materials into a mixer, adding water and stirring for 180 seconds to obtain a carbonated cement concrete mixture;
[0096] 3) pouring the mixture into a product mold to form the product, wherein the thickness of the product is 300 mm;
[0097] 4) Place the formed concrete in a dry environment for natural curing for 48 hours before removing the formwork, and then control the moisture content of the concrete product to 5% by drying;
[0098] 5) The obtained concrete product is placed in a carbonization reactor, first evacuated and then introduced with 100% concentration CO2 gas, the pressure in the reactor is controlled at 0.5 MPa and the temperature is 70°C, and carbonization curing is performed for 24 hours to obtain a carbonized cement concrete product.
[0099] After testing, the compressive strength of the concrete product before carbonization obtained in this comparative example is 6.6MPa before carbonization, 22.5MPa after carbonization, and the carbon fixation amount is 56kg / m 3 After further standard curing for one month, the compressive strength increased to 23.9MPa, and the pH value inside the test specimen was 12.5.
[0100] Comparative Example 2
[0101] A method for preparing carbonized concrete comprises the following steps:
[0102] 1) Weighing of raw materials, each component and its weight proportion are: 380 weight parts of cementitious material, 910 weight parts of fine aggregate, 920 weight parts of coarse aggregate, 165 weight parts of water, 3.0 weight parts of admixture (melamine water reducer);
[0103] The components and their mass percentages in the cementitious material used are: fast hydration active component A (C3A) 15%, high carbonization active component B (C3S2 and CS mixed in a mass ratio of 1:1) 71%, long-term hydration component C (β-C2S) 10%, and other components are mainly calcium aluminosilicate, iron phase solid solution and inevitable impurities;
[0104] 2) Add all the cementitious materials and all the fine aggregates into a mixer, add half of the water, close the mixer and introduce CO2 gas, so that the materials are fully stirred for 60 seconds in the CO2 atmosphere to obtain pre-carbonized cement mortar; wherein the mass of the introduced CO2 is 2% of the amount of cementitious materials;
[0105] 3) adding coarse aggregate, admixture and water to the obtained precarbonated cement mortar and stirring for 120 seconds to obtain a precarbonated low carbon cement concrete mixture;
[0106] 4) pouring the obtained mixture into a product mold to form the product, wherein the thickness of the product is 300 mm;
[0107] 5) Place the formed concrete in a dry environment for natural curing for 24 hours before removing the formwork, and then control the moisture content of the concrete product to 5% by drying;
[0108] 6) The obtained concrete product is placed in a carbonization reactor, first evacuated and then introduced with 100% concentration CO2 gas, the pressure in the reactor is controlled at 0.5 MPa and the temperature is 70°C, and carbonization curing is performed for 24 hours to obtain a carbonized cement concrete product.
[0109] After testing, the compressive strength of the concrete product before carbonization obtained in this comparative example is 28.4MPa before carbonization, 35.6MPa after carbonization, and the carbon fixation amount is 68kg / m 3 After further standard curing for one month, the compressive strength increased to 37.2MPa, and the pH value inside the test specimen was 11.7.
[0110] Comparative Example 3
[0111] A method for preparing carbonized concrete comprises the following steps:
[0112] 1) Weighing of raw materials, each component and its weight proportion are: 380 weight parts of cementitious material, 910 weight parts of fine aggregate, 920 weight parts of coarse aggregate, 165 weight parts of water, 3.0 weight parts of admixture (melamine water reducer);
[0113] The components and their mass percentages in the cementitious material used are: fast hydration active component A (C3A) 15%, high carbonization active component B (C3S2 and CS mixed in a mass ratio of 1:1) 71%, long-term hydration component C (β-C2S) 10%, and other components are mainly calcium aluminosilicate, iron phase solid solution and inevitable impurities;
[0114] 2) Add 2 / 3 of the cementitious material and all the fine aggregates into a mixer, add 2 / 3 of the water, close the mixer and introduce CO2 gas, stir the materials fully for 60 seconds under the CO2 atmosphere, and obtain pre-carbonized cement mortar; wherein the mass of the introduced CO2 is 2% of the amount of cementitious material;
[0115] 3) adding the remaining cementitious material, coarse aggregate, admixture and water to the obtained pre-carbonated cement mortar and stirring for 120 seconds to obtain a pre-carbonated low-carbon cement concrete mixture;
[0116] 4) pouring the obtained mixture into a product mold to form the product, wherein the thickness of the product is 300 mm;
[0117] 5) Place the formed concrete in a dry environment for natural curing for 24 hours before removing the formwork, and then control the moisture content of the concrete product to 6% by drying;
[0118] 6) The obtained concrete product is placed in a carbonization reactor, first evacuated and then introduced with 100% concentration CO2 gas, the pressure in the reactor is controlled at 0.5 MPa and the temperature is 70°C, and carbonization curing is performed for 24 hours to obtain a carbonized cement concrete product.
[0119] After testing, the compressive strength of the concrete product before carbonization obtained in this comparative example is 22.7MPa before carbonization, 38.5MPa after carbonization, and the carbon fixation amount is 76kg / m 3 After further standard curing for one month, the compressive strength increased to 40.7MPa, and the pH value inside the test specimen was 12.2.
[0120] By comparing Example 4 with Comparative Examples 1, 2, and 3, it can be seen that when pre-carbonization is not performed, the strength of the carbonized concrete before carbonization is low, which affects the demoulding of the concrete product, causes the phenomenon of missing edges and corners, and further affects the strength of the concrete after carbonization, and the carbon fixation capacity is also greatly reduced; when too much or even all cementitious materials are pre-carbonized, the prepared concrete mixture is dry, hard and loose, the vibration molding time is prolonged, and it is not easy to be dense. Although the concrete product has a high demoulding strength, due to the blockage of the carbonization channel, the subsequent carbonization potential is insufficient, and the carbonization mechanical properties and carbon fixation amount are reduced.
[0121] Obviously, the above preferred embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.
Claims
1. A carbonized concrete, characterized in that: The components and their weight proportions are: 280-600 parts of cementitious materials, 700-950 parts of fine aggregates, 800-1200 parts of coarse aggregates, 130-200 parts of water, and 2-12 parts of admixtures; wherein the cementitious materials include a hydration active component A, a high carbonization active component B, and a long-acting hydration component C; the hydration active component A is one or more of C3S, C3A, and C4A3Š, the high carbonization active component B is one or more of C3S2, CS, and γ-C2S, and the long-acting hydration component C is β-C2S; In the carbonized concrete, a part of the cementitious material and all the fine aggregate are first added to a part of the water, and CO2 gas is introduced for stirring to obtain a pre-carbonized cement mortar; and then the pre-carbonized cement mortar is mixed with the remaining cementitious material, coarse aggregate, admixture and remaining water to prepare a concrete mixture; The components in the gelling material and their mass percentages include: fast hydration active component A 10-20%, high carbonization active component B 50-80%, long-term hydration component C 10-30%; The partial amount of cementitious material accounts for 1 / 5 to 1 / 2 of the total amount of cementitious material; the partial amount of water accounts for 1 / 5 to 1 / 2 of the total amount of water; The mass of the CO2 gas is 1-5% of the amount of the cementitious material; The admixture is one or more of a naphthalene-based water reducer or a melamine water reducer.
2. The carbonized concrete according to claim 1, characterized in that: The fine aggregate is at least one of river sand, machine-made sand, river sand, and undersize material, with a fineness modulus of 2.0-3.2 and a powder content of more than 5wt%; the coarse aggregate is at least one of pebbles, crushed stones, and recycled aggregate; and a 5-31.5mm continuous grading or a 5-20mm continuous grading is adopted.
3. The carbonized concrete according to claim 1, characterized in that: The water reducing rate of the admixture is 15-30%.
4. The method for preparing carbonized concrete according to any one of claims 1 to 3, characterized in that: The steps include: 1) Weigh the raw materials according to the proportion. The components and their weight proportions are: 280-600 parts of cementitious materials, 700-950 parts of fine aggregate, 800-1200 parts of coarse aggregate, 130-200 parts of water, and 2-12 parts of admixtures; 2) Add part of the cementitious material and all the fine aggregate into the mixer, add part of the water, close the mixer and then introduce CO2 gas to fully stir the materials in the CO2 atmosphere to obtain pre-carbonized cement mortar; 3) adding the remaining amount of cementitious material, coarse aggregate, admixture and remaining water to the obtained pre-carbonated cement mortar, stirring and treating to obtain a pre-carbonated low-carbon cement concrete mixture; 4) pouring the mixture into the product mold to form; 5) Place the formed concrete body in a dry environment for natural curing, then remove the formwork and adjust the moisture content of the concrete body; 6) Carrying out carbonization curing on the obtained concrete body to obtain a carbonized cement concrete product.
5. The preparation method according to claim 4, characterized in that: The moisture content in step 5) is 3-7%.
6. The preparation method according to claim 4, characterized in that: In the carbonization curing process of step 6), the concentration of CO2 gas is 20~100%, the pressure is 0~1.2MPa, the temperature is 30~80℃, and the curing time is 6~24h.
Citation Information
Patent Citations
Method for preparing high-fixed-carbon-content construction material product
CN105801069A
Preparation method of carbon fixation concrete precast element
CN109485354A
Solid-waste-based high-activity carbon-sequestration low-calcium cementing material and preparation method thereof
CN114560639A
Low-carbon cement concrete and preparation method thereof
CN114873979A